The Management of Productive Waqf Land for Agriculture to Attain Sustainable Social Wellbeing (A Study of The Sub-Branch Administrator of Nahdlatul Ulama in Bumiayu of Malang City) - Gazi, Ananta; Ashar, Khusnul; Manzilati, Asfi (AIBPM Publisher, 2024)
Poverty is one of main issues, and the solutions for which are still being worked into. Waqf emerges as an instrument to reduce poverty and at the same time to improve public wellbeing. The objective of this research is to answer the question whether waqf has some degree of impacts on the three dimensions of welfare, i.e., income, health, and education, as seen from the roles of the recipients. Here qualitative method was used to answer the question. The data was harvested via interviews and documentation, and its credibility was preserved through triangulation. This study finds that sustainable social wellbeing has been achieved although the attainment only covers the basic needs due to the small economic scale and the absence of the element of modern agribusiness, which is an effort to increase the value of the agricultural product. The inhibiting factor lies in the branch-level management caused by non-procedural system administration, the non-performance of documentation, incompetent human resource, and small business capital. The originality of this study is observable in the attempt of answering whether waqf can become a solution for attaining sustainable social wellbeing and of seeking a management that can further increase the impact of waqf on the said social wellbeing